Libras enquanto língua de registro e circulação do conhecimento produzido no trabalho de conclusão de curso. - Souza, José Divino Mendes de (2022)
The present research is inserted in the field of Applied Linguistics and developed in an ethnographic perspective. Focusing on the elaboration of the Course Completion Work - TCC, at Modern Language: Brazilian sign language (LIBRAS) degree of the Federal University of Tocantins - UFT, the study has as general objective to outline theoretical possibilities embodied in the Language Policies for the elaboration of the TCC, considering the specificities of the Brazilian Sign Language – Libras. Therefore, the reflective sense is sought in the constructs of critical applied linguistics, with the aim of strengthening the circulation of Libras in the elaboration, presentation and publication of TCC`s. Theoretical reflections were built based on studies such as: Cavalcante e Silva, (2007); Erickson, (1985), Fritzen and Lucena, (2012); Gesser, (2012); Moita Lopes, (2013); Perlin, (2014, 2016); Quadros, (1997); Rajagopalan; (2003, 2007, 2010 and 2020); Stumpf, (2005). These are the main authors used in this research, in addition to observations made at the Federal University of Santa Catarina - SC, Florianópolis campus, a pioneer in Modern Language: Brazilian sign language (LIBRAS) degree, which provided the visualization of other possible ways for Deaf academics to develop the TCC. Based on these observations and observations in our applied field, which is the Modern Language: Brazilian sign language (LIBRAS) degree of the Federal University of Tocantins, I tried to reflect on different perspectives in relation to the Portuguese/written language dichotomy. That is, for many social groups, writing in oral languages is essential, however, for deaf people, graphocentrism combined with oral languages in contrast to sign languages, in which the ideology that writing is related to literacy and the school success. and they are synonymous with academic achievements and benefits. For the report of this work, the ethnographic perspective reverberated form of data generation, through document analysis, observations, interviews, field diary and photographs taken in pencil by one of the participants. In the analysis we explore the points of view of Deaf students and Deaf teachers as well as a professional sign language interpreter in which they are portrayed through interviews and field diary of the interaction and Deaf students and a professional in the field of interpretation and translation of signals in the TCC orientation and construction process. The results demonstrate that other possibilities of publishing academic works built by Deaf people are necessary, which can increase the circulation of knowledge with Libras as the protagonist language of the Deaf Community. The results demonstrate that other possibilities of publishing academic works built by Deaf people are necessary, which can increase the circulation of knowledge with Libras as the protagonist language of the Deaf Community. That is, it is necessary that Libras be the language of circulation of academic knowledge in the preparation, presentation and publication of the TCC.